Understanding how information and ICTs can improve health. (February 2012) - Bath, Peter A; Sen, Barbara A; Raptis, Dimitri A; Mettler, Tobias
The 15th International Symposium for Health Information Management Research (ISHIMR) was organized jointly by University Hospital Zurich (Switzerland), the University of St Gallen (St Gallen, Switzerland) and the University of Sheffield (Sheffield, UK). Participants included researchers, healthcare professionals, health service managers and planners. The aim of the ISHIMR series of conferences is to bring together researchers and practitioners to disseminate, share and discuss research into how information and communication technologies can improve the management of information with the health sector.